2017
DOI: 10.7287/peerj.preprints.2840v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The landscape of fear conceptual framework: definition and review of current applications and misuses

Abstract: Landscapes of Fear (LOF), the spatially explicit distribution of perceived predation risk as seen by a population, is increasingly cited in ecological literature and has become a frequently used "buzz-word". With the increase in popularity, it became necessary to clarify the definition for the term, suggest boundaries and propose a common framework for its use. The LOF, as a progeny of the "ecology of fear" conceptual framework, defines fear as the strategic manifest of the cost-benefit analysis of food and sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 0 publications
0
36
0
Order By: Relevance
“…It was recently postulated that this temporal partitioning may be a result of reciprocal coevolutionary changes in predation and antipredator behaviors (Wu, Wang, Wang, & Feng, ). Hence, spatiotemporal behavioral patterns in mammals have an evolutionary component which may play a role in the “ecology of fear” model (Bleicher, ). Within this model, a variety of behavioral strategies are described for prey species to minimize predator encounter rates and the risk of attacks.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently postulated that this temporal partitioning may be a result of reciprocal coevolutionary changes in predation and antipredator behaviors (Wu, Wang, Wang, & Feng, ). Hence, spatiotemporal behavioral patterns in mammals have an evolutionary component which may play a role in the “ecology of fear” model (Bleicher, ). Within this model, a variety of behavioral strategies are described for prey species to minimize predator encounter rates and the risk of attacks.…”
Section: Discussionmentioning
confidence: 99%
“…Brown (1988) framed the harvest rate an animal makes at a given patch as a balance of the energetic gains and costs attributed to foraging effort, predation, and missed opportunity costs. The GUD, as a method, has been ❖ www.esajournals.org adapted to test a large variety of elements affecting the strategic decisions animals take (Bedoya-Perez et al 2013) and has been widely applied as a measure for habitat use (Yl€ onen et al 2002, Orrock et al 2004, Bleicher 2017, Bleicher et al 2018. The GUD, as a method, has been ❖ www.esajournals.org adapted to test a large variety of elements affecting the strategic decisions animals take (Bedoya-Perez et al 2013) and has been widely applied as a measure for habitat use (Yl€ onen et al 2002, Orrock et al 2004, Bleicher 2017, Bleicher et al 2018.…”
Section: Experimental Design-behavioral Assaysmentioning
confidence: 99%
“…GUD methods have been used with wild primates to examine differences in perceived predation risk between microhabitats (Emerson et al, ; Makin et al, ) and risk from humans on foraging trade‐offs (Nowak, Hill, et al, ; Nowak, Richards, ; Nowak et al ). Nowak et al () used these methods with habituated animals and found that when not in proximity to an observer, individuals tended to forage less from the ground, suggesting the presence of a “human shield.” From a conservation standpoint, GUD experiments are likely to be most useful when they can serve as an indicator of habitat selection in anthropogenically altered environments in which human activity might alter food availability, predator density, or habitat structure (Bleicher, ). For example, GUDs have been used in non‐primate taxa to assess which habitats serve as refuges (Carter & Bright, ) and to contrast foraging behavior in fragmented or degraded habitats with more pristine environments (Whelan & Jedlicka, ).…”
Section: Discussionmentioning
confidence: 99%